2004
DOI: 10.1002/mus.20083
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia sensitivity and motoneuron afterhyperpolarization in human motor units

Abstract: The purpose of this study was to examine whether motor units, grouped by speed of contraction in the human first dorsal interosseous muscle, differed in their sensitivity to ischemia and motoneuron afterhyperpolarization (AHP) time-course. Motor units were recorded while subjects held an abduction force for approximately 10 min. Subsequently, subjects abducted for 4-5 min under ischemic conditions. Motor unit twitches derived using spike-triggered averaging were allocated into "fast" or "slow" contracting grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Since contraction-related ischaemia can be considered comparable between our two groups of athletes, and since slow motor units have a greater sensitivity to ischaemia than fast motor units (Gossen, Ivanova, & Garland, 2004), our findings also suggest that the estimation of conduction velocity overshooting may be used to distinguish participants with different muscular properties.…”
Section: Myoelectric Responses To Exercisementioning
confidence: 92%
“…Since contraction-related ischaemia can be considered comparable between our two groups of athletes, and since slow motor units have a greater sensitivity to ischaemia than fast motor units (Gossen, Ivanova, & Garland, 2004), our findings also suggest that the estimation of conduction velocity overshooting may be used to distinguish participants with different muscular properties.…”
Section: Myoelectric Responses To Exercisementioning
confidence: 92%
“…Nevertheless, studies on rat muscles have shown a greater decline in twitch force in slow muscle than in fast muscle during the first 45 minutes of ischemia, particularly during the first 15‐30 minutes . Likewise, Gossen et al reported markedly greater declines in twitch force in slow contracting motor units than in fast units during very low‐force (~5%‐10% of MVC) voluntary ischemic contractions in human subjects.…”
Section: Fatigue and Recovery In The Muscle Fibre Types With Ischemicmentioning
confidence: 99%